Development of a smartphone camera-based chemiluminescent lateral flow immunoassay for detecting African swine fever virus antibodies - Sun, Yaning; Yang, Suzhen; Xing, Yunrui; Fan, Lu; Wang, Nannan; Li, Qingmei; Guo, Junqing; Qiao, Songlin; Zhang, Gaiping (Frontiers in Microbiology, 2025)
African swine fever (ASF) is a highly contagious viral disease threatening global swine industries. Rapid and accurate detection of ASF virus (ASFV) antibodies is crucial for disease surveillance and control. The gold lateral flow immunoassay (GLFIA) is cost-effective and has been successfully applied in rapid on-site detection of ASFV. However, its sensitivity is relatively low. To enhance the detection sensitivity and accuracy while retaining convenience, we developed a chemiluminescent lateral flow immunoassay (CLFIA) for detecting ASFV antibodies based on the p72 trimer protein, which can immediately read the chemiluminescent signal through the camera of a smartphone. Compared with GLFIA and commercial enzyme-linked immunosorbent assay (ELISA), its sensitivity was improved by at least two orders of magnitude and nine orders of magnitude, respectively. Additionally, CLFIA shows no cross-reaction with antibodies from common swine disease viruses, and the detection results of 65 clinical samples have a 93.8% coincidence rate with those of commercial ELISA kits. This research successfully addressed the issue that traditional chemiluminescent detection relies on specialized instruments, providing a new technical approach for the highly sensitive and rapid detection of ASFV, and effectively promoting the development and application of CLFIA technology.